Workers of the Internet unite? Online freelancer organisation among remote gig economy workers in six Asian and African countries - Wood, A; Lehdonvirta, V; Graham, M (Wiley, 2018)
This article presents findings regarding collective organisation among online freelancers in middle‐income countries. Drawing on research in Southeast Asia and Sub‐Saharan Africa, we find that the specific nature of the online freelancing labour process gives rise to a distinctive form of organisation, in which social media groups play a central role in structuring communication and unions are absent. Previous research is limited to either conventional freelancers or ‘microworkers’ who do relatively low‐skilled tasks via online labour platforms. This study uses 107 interviews and a survey of 658 freelancers who obtain work via a variety of online platforms to highlight that Internet‐based communities play a vital role in their work experiences. Internet‐based communities enable workers to support each other and share information. This, in turn, increases their security and protection. However, these communities are fragmented by nationality, occupation and platform.